Biofuel production using Pd/Zn synergistically catalyzed hydrodeoxygenation applied at bio oil extracted in biomass pyrolysis process. (10th May 2016) - Huang, Yinbin; Wei, Lin; Zhao, Xianhui; Julson, James; Qiu, Changling; Dharmarajan, Shanmugapriya; Kiratu, John; Raynie, Douglas; Dubey, Ashish; Qiao, Qiquan
Summary: Raw bio oil includes multicomponents. In order to avoid the interference between complex reactions, the model compounds, instead of the real bio oil, have been widely used for the study of raw bio‐oil upgrade. In this work, the hydrodeoxygenation (HDO) of raw pine pyrolysis bio oil was investigated at 200 °C using Pd/Zn synergistic catalysis under hydrogen pressures of 200, 300, and 400 psi, separately. The resulting product included gas, liquid, and coke. The gas was characterized using a gas chromatography. The liquid was characterized using a gas chromatography–mass spectrometry. The results showed that the HDO performance achieved promotion to some extent by the Pd/Zn synergistic catalysis compared with use of Pd/C or Zn 2+, independently. The HDO also gave rise to improvements on physicochemical properties of bio oils. Notably, the highest water content (13.16 wt%) revealed that deoxygenation reaction could be promoted by Pd/Zn synergistic catalysis compared with use of Pd/C or Zn 2+, independently. More importantly, the highest hydrocarbon yield (19.15% on the base of liquid part) could be obtained by the treatment of 300 psi pressure and 200 °C temperature over Zn/Pd/C synergistic catalysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : After being dissolved with the same amount of methanol, the raw bio‐oil undergoes hydrodeoxygenation reactions with the presence of Pd/C + ZnCl2 catalyst in a high‐pressure reactor. The hydrodeoxygenation reactions produce three products: syngas, solid (carbon deposits), and liquid biofuel.